NATURE OF ATMOSPHERIC GLOW DURING EARTHQUAKES - Grigor'yev A.I.; Gokhberg M.B.; Gershenzon N.I. (My University, 1988)
The paper demostrates that the atmospheric glow phenomenon can be attributed to instability of droplets in a haze (or rain or drizzle) or thawed ice crystals (or rime) in an electric field. The instability results from an increase in the amplitude of capillary waves. In the linear stage of its development, projections form on the tops of the droplets and emit smaller, charged droplets. Ultimately, the haze cloud begins to glow in the entire zone where the instability condition is satisfied. The external electric field strength needed for this to occur is smaller, and under certain conditions much smaller, than the field that generates breakdown in the absence of droplets. A significant decrease in the critical field value can occur in the presence of additional factors accompanying the concluding state of earthquake preparation.